Understanding degradation in lithium-ion and lithium-air batteries - McNulty, Rory (2023)
With a global transition towards electrification, there is considerable interest in the development of high energy density battery technologies. The current world leading battery chemistries, that are enabling the mass market electrification of transport, are high-nickel positive electrodes. However, as positive electrode nickel-content increases, so too does the reactivity of the positive electrode surface with the electrolyte species, limiting the long-term performance of these cell chemistries. The purpose of the first half of this thesis is to identify failure mechanisms and understand the feasibility of vinylene carbonate formation in cells containing a NMC811 electrode, with the objective of proposing actionable solutions to overcome current inefficiencies hindering research progress. To enable the electrification of next-generation applications, technologies that far exceed the possible performance of traditional lithium-ion batteries are required. The latter half of this thesis examines the degradation of the lithium-air battery, a technology with a theoretical specific capacity ten times greater than traditional lithium-ion. The purpose of this work was to understand the role of H2O, and the hydroperoxide species that are introduced by its presence, in chemical and electrochemical degradation reactions. Here hydroperoxide species are directly identified as playing an antagonistic role in the chemical degradation of acetonitrile, and in the electrochemical formation of lithium hydroxide, the mechanism of which is conclusively identified for the first time.